The failure of democracy in Turkey: a comparative analysis - McLaren, Lauren M.; Cop, Burak (Wiley-Blackwell, 2011)
Although Turkey took its initial steps toward establishing democracy in 1950, it has thus far failed to become a fully functioning democracy. Using the comparison cases of Spain and Greece, this paper discusses two related variables that are likely to have thwarted the development of full democracy in Turkey: (1) experience with authoritarian rule and (2) elite settlement or convergence toward acceptance of the democratic rules of the game. The paper ultimately contends that despite the EU’s attempt to push Turkey towards full democracy in the modern day it is unlikely that Turkey will become a fully functioning democracy until it manages to achieve civilian elite agreement regarding the rules of the Turkish democratic game, and that Turkey’s experience with authoritarian rule may, in turn, have hindered the development of such rules.